On certain fractional integral operators of two variables and integral transforms - Khan, Mumtaz Ahmad; Salama Abukhammash, Ghazi (Pro Mathematica, 2003)
The present paper is in continuation to authors earlier paper 9 where two variable analogues of certain fractional integral operators of M. Saigo were investigated. This paper deals with the effect of operating two variable analogues of Mellin and Laplace transforms on these two variable analogues of fractional integral operators of the earlier paper.